2021
DOI: 10.3390/jcm10132988
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Oral Versus Intravenous Bisphosphonate Administration on Osteoclastogenesis in Advanced-Stage Medication-Related Osteonecrosis of the Jaw Patients

Abstract: It is yet unknown whether the intravenous administration route alone can fully account for the exacerbation of medication-related osteonecrosis of the jaw (MRONJ). The purpose of this retrospective study was to identify the potential role of the bisphosphonate (BP) administration route as an independent prognostic factor for non-cancerous, stage III MRONJ patients. Bone samples were retrospectively obtained from two groups of osteoporosis patients who underwent surgery for the treatment of stage III MRONJ. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…However, compensatory stimulation of osteoclastogenesis and even increased osteoclast number could be observed at different stages of MRONJ [21]. In one study, cultures of the necrotic MRONJ lesions expressed giant, hypernucleated osteoclasts [22]. Recent studies have suggested the direct effects of anti-resorptive medications on oral immune cells [23] and periodontal ligament stem cells [24,25].…”
Section: Anti-resorptive Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compensatory stimulation of osteoclastogenesis and even increased osteoclast number could be observed at different stages of MRONJ [21]. In one study, cultures of the necrotic MRONJ lesions expressed giant, hypernucleated osteoclasts [22]. Recent studies have suggested the direct effects of anti-resorptive medications on oral immune cells [23] and periodontal ligament stem cells [24,25].…”
Section: Anti-resorptive Medicationsmentioning
confidence: 99%
“…Recent studies have suggested the direct effects of anti-resorptive medications on oral immune cells [23] and periodontal ligament stem cells [24,25]. Patients receiving IV bisphosphonates have higher bone OPG and lower TRAP and RANKL expression levels, which could signify an impaired osteoclast activation by other bone cells, such as osteoblasts and osteocytes [22,26]. Experimental and clinical studies have shown that steroid therapy, nicotine smoking, and associated systemic pathologies, such as dia-betes or inflammatory joint pathology, increased the risk of MRONJ with bisphosphonate treatment [27,28].…”
Section: Anti-resorptive Medicationsmentioning
confidence: 99%
“…We cannot be conclusive that the differences are caused by the route of administration alone; other factors, such as differing health conditions of patients who require IV or oral bisphosphonates could also play a role. However, a recent study has found that IV administration of bisphosphonates seem to have a greater effect on osteoclastic activity-compared to oral bisphosphonates at the same dosage-that seems to "aggravate" the conditions of BRONJ [91].…”
Section: Administration Routes and Effect On Dental Proceduresmentioning
confidence: 99%
“…Bisphosphonate administration can be done orally and intravenously. Oral administration uptake shows only 1% absorbance into the gastrointestinal tract and intravenous (IV) shows an absorption rate of over 50% [16]. The prevalence of BRONJ in osteoporosis patients with the administration of bisphosphonates is known to range from 0% to 0.04%, and some papers show a prevalence of less than 0.001% [17,18].…”
Section: Antiresorptive Medicationsmentioning
confidence: 99%